Inside Cover: Synthesis of Renewable meta‐Xylylenediamine from Biomass‐Derived Furfural (Angew. Chem. Int. Ed. 33/2018). Issue 33 (6th July 2018) - Scodeller, Ivan; Mansouri, Samir; Morvan, Didier; Muller, Eric; de Oliveira Vigier, Karine; Wischert, Raphael; Jérôme, François
Abstract : Functionalized aromatic chemicals have been produced from furfural, a building block available on a large scale from low‐cost biomass. In their Communication on page 10510 ff., R. Wischert, F. Jérôme et al. report their strategy that relies on a Diels–Alder/aromatization sequence. By controlling the rate of each step, it was possible to produce exclusively the meta aromatic isomer. meta ‐Xylylenediamine was synthesized.